Classification of Isolates from the Pseudomonas fluorescens Complex into Phylogenomic Groups Based in Group-Specific Markers - Garrido-Sanz, Daniel; Arrebola, Eva; Martínez-Granero, Francisco; García-Méndez, Sonia; Muriel, Candela; Blanco-Romero, Esther; Martín, Marta; Rivilla, Rafael; Redondo-Nieto, Miguel (Frontiers in Microbiology, 2017)
The Pseudomonas fluorescens complex of species includes plant-associated bacteria with potential biotechnological applications in agriculture and environmental protection. Many of these bacteria can promote plant growth by different means, including modification of plant hormonal balance and biocontrol. The P. fluorescens group is currently divided into eight major subgroups in which these properties and many other ecophysiological traits are phylogenetically distributed. Therefore, a rapid phylogroup assignment for a particular isolate could be useful to simplify the screening of putative inoculants. By using comparative genomics on 71 P. fluorescens genomes, we have identified nine markers which allow classification of any isolate into these eight subgroups, by a presence / absence PCR test. Nine primer pairs were developed for the amplification of these markers. The specificity and sensitivity of these primer pairs were assessed on 28 field isolates, environmental samples from soil and rhizosphere and tested by in silico PCR on 421 genomes. Phylogenomic analysis validated the results: the PCR-based system for classification of P. fluorescens isolates has a 98.34% of accuracy and it could be used as a rapid and simple assay to evaluate the potential of any P. fluorescens complex strain.